Analisis Faktor-Faktor Yang Mempengaruhi Kemauan Pelaku Usaha Mikro, Kecil, Dan Menengah Dalam Membayar Pajak Penghasilan Dengan Tingkat Kepercayaan Sebagai Variabel Moderasi (Studi Kasus Pelaku UMKM Di Kecamatan Bandar) - Arrazak, Dicky (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the factors that influence the willingness of Micro, Small and Medium Enterprises to pay income taxes with rate of trust as a moderating variable in Bandar District, Simalungun Regency. The sample selection method used was purpos e sampling with sample size calculation using the Slovin formula. The total observations in this study were 100 MSME. The data analysis technique used in this research is the residual test using the SPSS 26 analysis tool. The results of this study show that the variables of tax socialization, understanding of taxation, good perception of the effect eness of the taxation system simultaneously and significantly influence the willingness to pay taxes. Partially, the rate of trust, tax socialization, understanding of taxation, and good perception of the effect eness of the tax system significantly influence the willingness to pay taxes. The rate of trust is able to moderate the influence of tax socialization and understanding of taxation, but disable to moderate good perceptions of the effect eness of the taxation system on the willingness to pay taxes.